Evaluasi Penerapan Konsep Bangunan Hijau Berdasarkan Peraturan yang Berlaku pada Sebuah Bangunan Gedung Perkantoran di Kawasan Industri Jakarta Timur - Aji Nagoro, Gurid; Widjajanti, Endang; Hendra Padangalam, Johannes (Sci-tech Journal, 2026)
This thesis presents measurements related to the application of green building concepts to an office building in East Jakarta. The measurement results obtained are then used to determine the building's rating criteria against applicable regulations. The green building concept is a building concept that is designed, constructed, and operated with consideration for its impact on the environment and human health, as well as aiming to conserve energy. Regulations regarding green buildings in Indonesia are currently issued by the Green Building Council Indonesia (GBCI), the Ministry of Public Works and Public Housing, regional governor regulations in several regions, and technical guidelines from several other ministries. Green building measurements can be made in three stages, namely the design stage, the built condition stage, and the operation stage. The research was conducted through a case study of an office building in East Jakarta. The research resulted in a green building rating based on a review of GBCI V.12 regulations and PUPR Regulation No. 21 of 2021, as well as the amount of electricity and water savings that can be achieved based on the baseline from the Roadmap for the Implementation and Development of Green Buildings (2023). This building received 59 points out of 101 under the GBCI V.12 regulations and was categorized as gold. In the review of the Minister of Public Works and Public Housing Regulation, it scored 125 out of 165 points and falls into the medium green building category. With this implementation, electricity energy efficiency of 29.737% can be achieved, water savings of 12.63% based on the PUPR baseline standard, and a reduction in carbon emissions of 956,457.904 kg CO2e.